Effect of Organizational Climate on Lecturer Performance - Subai, Subai; Hanafi, Syadeli; Hidayat, Sholeh (Journal of Educational Analytics, 2024)
A company's most important asset is its people since they contribute vitality, talent, creativity, and effort. One of the educational subsystems that is essential to producing human resources of the highest caliber is higher education. In the context of higher education, lecturers play a crucial role in shaping the caliber of students who graduate, the caliber of the educational process, and the caliber of higher education as a whole. The outcomes of any educational program, no matter how good, will be unsatisfactory if the program is not backed by excellent instructors. This study aims to investigate and develop a model of how lecturer competency, individual characteristics, and organizational environment affect performance through lecturers' individual commitment.